STATE FORMATION OF WOLAITTA AND ITS KINGDOM UP TO 1894 - Lambebo, Abesha Shirko; Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
This study portrays state formation of Wolaitta and its kingdom up to 1894. The main factors that led to state formation of Wolaitta were the developments of socio-cultural and economic dynamics which was related with the settlement in Omo River Valley since the time Neolithic Revolution. The socio-cultural dynamics such as clan development, conflict, control to lead the area and others. The economic dynamics include the beginning of agriculture due to sedentary way of life in Omo River Valley. These dynamics led to the clan union as well as divergence, leadership practice, agriculture, trade and the like. The study moves on to a discussion of the process of state formation of Wolaitta and its kingdom that established various dynasties. The state formation of Wolaitta implicated the rise of strong kingdom and highlights state structure. Finally, the study identifies rather intriguing topics for further inquiry.